2005
DOI: 10.1038/sj.npp.1300771
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Object Recognition Memory Following Methamphetamine, but not p-Chloroamphetamine- or d-Amphetamine-Induced Neurotoxicity

Abstract: Repeated moderate doses of methamphetamine (mAMPH) damage forebrain monoaminergic terminals and nonmonoaminergic cells in somatosensory cortex, and impair performance in a novelty preference task of object recognition (OR). This study aimed to determine whether the memory deficit seen after a neurotoxic mAMPH regimen results from damage to dopamine (DA) and/or serotonin (5-HT) terminals. Animals were given a neurotoxic regimen of mAMPH, p-chloroamphetamine (PCA, preferentially damages 5-HT terminals), dampheta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 55 publications
14
92
3
Order By: Relevance
“…Recognition of the spatial reconfiguration was spared, and there were no effects on overall locomotor activity between groups. The present findings are congruent with previous reports of impairments in novel object recognition resulting from acute, non-contingent methamphetamine injections (Belcher et al 2005;Bisagno et al 2002;Schroder et al 2003). While the reduced interaction with the novel object can be interpreted as a deficit in recognizing a novel object, it is also possible that animals with a history of chronic methamphetamine intake have reduced motivation to interact with a novel object during the task.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recognition of the spatial reconfiguration was spared, and there were no effects on overall locomotor activity between groups. The present findings are congruent with previous reports of impairments in novel object recognition resulting from acute, non-contingent methamphetamine injections (Belcher et al 2005;Bisagno et al 2002;Schroder et al 2003). While the reduced interaction with the novel object can be interpreted as a deficit in recognizing a novel object, it is also possible that animals with a history of chronic methamphetamine intake have reduced motivation to interact with a novel object during the task.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of repeated methamphetamine exposure in animals have demonstrated impairments in sequential motor learning (Daberkow et al 2005), increased impulsivity (Richards et al 1999), and decreased novel object recognition (Belcher et al 2005;Kamei et al 2006). However, these studies have all utilized non-contingent, short-term drug administration, an approach that does not approximate the contingent, long-term drug use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…While it might be suspected that rats exposed to doses of ( + )-methamphetamine that produce seizures and neurotoxicity would have nonspecific behavioral alterations, the contrary is more apparent. For example, novel object recognition is impaired in animals treated with ( + )-methamphetamine; however, novel place recognition and spatial learning and memory are intact (Belcher et al, 2005;Bisagno et al, 2002;Friedman et al, 1998;Schroder et al, 2003). It should be noted that Friedman et al (1998) showed that animals treated with ( + )-methamphetamine had a small deficit in latency to the platform in the MWM, but this was only apparent on one of the 5 days tested and no differences were noted in the probe phase.…”
Section: Effects Of 5-meo-diptmentioning
confidence: 98%
“…The perirhinal cortex can also sustain dopaminergic transmission (Pum et al, 2007); it expresses D1 and D2 dopamine receptors across all layers (Richfield et al, 1989;Goldsmith and Joyce, 1994), D4 receptors (Rivera et al, 2008) and dopamine transporters (Belcher et al, 2005). Based on several tracing studies, there are low levels of GABAergic input to the perirhinal cortex (Christie et al, 1987;Kosaka et al, 1987;Beart et al, 1990;Vaucher et al, 2000) but GABAergic inputs from the temporal and entorhinal cortices have been identified (Garden et al, 2002).…”
Section: Neurotransmission In the Perirhinal Cortexmentioning
confidence: 99%
“…Finally, the perirhinal cortex receives serotoninergic input (Pum et al, 2007) with a projection from the raphe nucleus terminating in superficial layers of the perirhinal cortex (Hermann et al, 1997;Vertes et al, 1999;Harding et al, 2004). The perirhinal cortex expresses 5-HT 1A receptors (Nyakas et al, 1997), 5-HT 2 receptors (Altar et al, 1985;Osterlund et al, 1999) and 5-HT transporters (Hé bert et al, 2001;Belcher et al, 2005). In addition to the classic neurotransmitters, the perirhinal cortex is also capable of signalling via the neurotrophins and their receptors (Sobreviela et al, 1996).…”
Section: Neurotransmission In the Perirhinal Cortexmentioning
confidence: 99%